The Meaning of Money and Its Influence on Decision To Take A Loan: Study on Members of Credit Union - Hartanti, Fransisca Emi; Kusumajati, Titus Odong (Journal of Entrepreneurship & Business, 2025)
Purpose: This study aims to elaborate on how credit union members perceive money and how these perceptions inform the decision made before applying for a loan from a credit union. Method: The study employed grounded theory as its methodology. Data were obtained from in-depth, semi-structured interviews and observations involving ten members of a credit union in Indonesia. This research's respondents are divided into two types: the first lists respondents who actively borrow (five respondents), and the second lists those who do not (five respondents). Result: The study shows two categories in which money is perceived: money as a resource and money as a source of emotions. The study further found that six key factors inform the decision to apply for a loan. Past experiences (1) contribute to the meaning of money (2) and perceptions toward loans (3). Further, pressing needs (4) not accompanied by financial strength (5) to finance them result in motives for procuring loans. With access to loans (6), motives can turn into an action of taking out a loan. Based on the findings, Credit unions should perform a thorough analysis to identify pressing needs among their members and evaluate the access to loans regarding their capacity to fulfill the members' needs. Furthermore, loans should be conveyed as a means to achieve financial goals and improve the members' quality of life.